Will Washington Kick-start the U.S. Battery Biz?. - Voelcker, J. (IEEE spectrum)
During his presidential campaign, Barack Obama promised to put 1 million plug-in hybrids and electric vehicles on U.S. roads by 2015, one of several steps toward energy independence. But getting there, say auto industry analysts, will require a heavy dose of government intervention and, crucially, the rapid construction of a domestic industry to manufacture advanced batteries. U.S. industry groups are pushing strongly for both.